2000
DOI: 10.1175/1520-0493(2000)128<0322:eiotri>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on the Rapid Intensification of Hurricane Opal (1995) over the Gulf of Mexico

Abstract: Hurricane Opal intensified rapidly and unexpectedly over the Gulf of Mexico between 1800 UTC 3 October and 1000 UTC 4 October 1995. During this period the storm central pressure decreased from 963 to 916 hPa and sustained winds reached 68 m s Ϫ1. Analyses that include high-resolution GOES-8 water vapor winds and European Centre for Medium-Range Weather Forecasts (ECMWF) and National Centers for Environmental Prediction (NCEP) gridded datasets are employed to examine the rapid intensification phase of Opal. Opa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
123
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(129 citation statements)
references
References 57 publications
5
123
1
Order By: Relevance
“…It is known that the large-scale environmental conditions such as vertical wind shear and upper level trough or cold low dynamics and thermodynamics in the inner core region, and air-sea interactions all play important roles in determining the intensity change (Davis and Emanuel 1988;Merrill and Velden 1996;Willoughby and Black 1996;Bosart et al 2000;Nolan et al 2007;Shay et al 2000). Among all these factors, the processes occurring in the inner core are closely associated with the parameterization schemes in numerical models.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the large-scale environmental conditions such as vertical wind shear and upper level trough or cold low dynamics and thermodynamics in the inner core region, and air-sea interactions all play important roles in determining the intensity change (Davis and Emanuel 1988;Merrill and Velden 1996;Willoughby and Black 1996;Bosart et al 2000;Nolan et al 2007;Shay et al 2000). Among all these factors, the processes occurring in the inner core are closely associated with the parameterization schemes in numerical models.…”
Section: Introductionmentioning
confidence: 99%
“…Atallah and Bosart [2003] showed that the baroclinic zone between the juxtaposition of a cold-core potential vorticity (PV) anomaly associated with the midlatitude trough and a warm-core PV anomaly associated with a tropical cyclone provided sufficient precipitation in a region favorable for deep isentropic ascent. Through an interaction with the synoptic environment referred to as an extratopical transition, typhoons also can be reintensified or dissipated [Klein et al, 2000;Harr and Elsberry, 2000;Bosart et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…1). During the same period, an upper-tropospheric westerly trough was approaching from the west to the northern Gulf of Mexico, which may have affected the intensification (Bosart et al 2000).…”
Section: Introductionmentioning
confidence: 99%